OTOVAKSIN SEBAGAI TERAPI ALTERNATIF INFEKSI MYCOBACTERIUM TUBERCULOSIS PADA TIKUS PUTIH (RATTUS NORVEGICUS) - Praseno, Praseno; Nurrokhman, Nurrokhman; Fiatiningsih, Istiana (Lembaga Penelitian Universitas YARSI, 2007)
Tuberculosis (TB) is still an important public health problem, especially in developing countries such as Indonesia. Efforts have been made to overcome the problem, however, number of cases is still high. This is due to various factors which might affect the development of the disease. Increasing number of resistant strains against antimycobacterial drugs is one of the major factors. Therefore, alternative method to control TB is needed.The aim of this study was to evaluate the effectiveness of autogenous vaccine on healing process of infection caused by Mycobacterium tuberculosis in rats. Eighteen Wistar rats (Rattus norvegicus) were infected with 109 colony forming unit of M. tuberculosis subcutaneously. One week after infection, the rats were divided randomly into 2 groups, first group were treated with autogenous vaccine and the other were left untreated (control group). Autogenous vaccine was given subcutaneously with the dose of 108 cfu/0,1 ml every 7 days 3 times. Subcutaneous nodules were evaluated every 3 days and weight gain was evaluated 3 times. Laboratory examinations were done, including acid fast bacilli stain, histopatological feature and serologic test. The result showed that recovery of subcutaneous nodules in autovaccine treated group of rats was faster than that of untreated control group. Acid fast bacilli staining showed that the number of micobacteria found in the lung, liver, spleen and kidney of autovaccine treated group were much lower than those found in the control group. Histopathology features showed that lymphocytes infiltration in the lung and other organs was heavier in the control group than that of treated group. In conclusion, animal study on rats showed that autogenous vaccine had effective therapeutic effect on healing process for M. tuberculosis infection.